Ethnobotany and cultural resistance: liturgical use of plants in Umbanda and Candomblé temples in Foz do Iguaçu (Research, Society and Development, 2025)
The objective of this study was to describe the liturgical use of plants in Afro-Brazilian religious temples in Foz do Iguaçu (Paraná, Brazil), with emphasis on ethnobotanical implications. This cross-sectional descriptive survey (May–October 2024) was conducted through semi-structured interviews with leaders of three temples (two Umbanda and one Candomblé). The questionnaire addressed participants’ profiles, the foundations of the temples, and the plant species employed, including preparation and use, symbolic meanings, and origin or acquisition routes. Responses were categorized and analyzed descriptively. A total of 81 species used in rituals were identified; the most frequent categories were “spiritual cleansing/discharge” (45.5%) and “spiritual protection” (42.9%), followed by harmony/calmness, spiritual connection, healing of ailments, luck/prosperity, and path opening. Socioeconomic factors and the urban context limited cultivation and collection, increasing dependence on external suppliers; plant management was regulated by internal hierarchy and ritual authorization. The systematic documentation of traditional knowledge supports biocultural conservation and informs municipal actions – such as community gardens, protection of collection areas, and health education – thus contributing to countering religious intolerance and to valuing traditional practices within the territory.